The effectiveness of ISALS in improving agricultural productivity among rural smallholder farmers. the case of ward 10 and 11 of Shurugwi District. - Munyangiri, Enerst (Midlands State University, 2020)
Microfinance programs such as ISALs has become an imperative tool in empowering rural poor people by reducing poverty levels across the globe. The assumption is that by inculcating a culture of saving and improving their access to credit, rural poor people will be able to establish income generating activities that is aimed at reducing poverty through enhancing agricultural productivity at all levels. Literature has shown that as a result of its affordability and accessibility, the ISALs model or methodology have become very popular with the rural population. The main objective of this study was therefore to assess the effectiveness of ISALs in improving agricultural productivity among rural small scale holder farmers. The study used Wards 10 and 11 of Shurugwi District, Midlands Province as a case study. The researcher utilized a mixed research method which provided strengths that counterbalance the weaknesses of both qualitative and quantitative research enhancing a rich study findings. Sampled ISAL participants and key informants interviewees provided rich data that informed the study findings. The study established that participation in ISALs have a statistically significant positive impact on agricultural productivity. Evidence of improved agricultural production has been shown through increased yield per hectare which was necessitated by improved access to inputs and farming implements among others. The study has recommended an all-inclusive and harmonized approach by all relevant stakeholders in the development field that will create an enabling environment for ISALs to realize more positive impact in boosting agricultural productivity.